Returning to a land of opportunity? Effects of land restitution in Colombia - Crowther, N; Klymak, M (University of Oxford, 2022)
Millions of people are internally displaced by wars and conflicts with wide-ranging adverse social and economic consequences. Yet, we still know very little about how they fare upon return to their homes. Colombia’s 50-year internal armed conflict resulted in the world’s highest number of internally displaced people. In this paper, we study the effects of a recently implemented law allowing displaced Colombians to apply to receive land restitution. Although everyone could apply for restitution immediately, the implementation of claims happened in a phased manner. Using agricultural census data coupled with geospatial location of formal land restitution, and individual level information on applications, we shed light on the effect of land restitution on three sets of outcomes: social integration, labour investments and market integration. Our results suggest restituted households are integrating into the community - they are more likely to be a member of an association, more likely to partake in reciprocal farm work and sell their produce. We also find evidence that in the short run, unlike the findings in the literature relating to land formalisation, restituted households are not more likely to hire permanent workers but instead increase the use of day workers and household members on their land.